Implementasi Sistem Informasi Desa untuk Meningkatkan Transparansi dan Pelayanan Publik di Desa Tertinggal - I Gede Arya Pramana (Journal of Community Action, 2025)
The implementation of village information systems (VIS) has become an essential initiative in supporting transparent governance and improving public services at the village level, particularly in underdeveloped regions. This study aims to analyze the effectiveness of VIS in enhancing administrative transparency and public service quality in underdeveloped villages in Bali Province. Using a mixed-method approach combining qualitative interviews and quantitative surveys, data were collected from 120 respondents consisting of village officials, community representatives, and local residents in three pilot villages implementing VIS. The results indicate a significant improvement in information accessibility, administrative efficiency, and citizen participation following the adoption of VIS. Statistical analysis reveals a positive correlation between VIS usage intensity and perceived service transparency (r = 0.76, p < 0.05). Qualitative findings further highlight the role of digital literacy and community engagement as key enablers of successful VIS adoption. The study concludes that VIS implementation not only enhances accountability and governance efficiency but also fosters social trust between local governments and citizens. Recommendations are provided to strengthen digital capacity building and ensure the sustainability of VIS initiatives in rural contexts.